BHANGKA MBULE-MBULE: TRADISI TOLAK BALA PADA MASYARAKAT DI KELURAHAN MANDATI KECAMATAN WANGI-WANGI SELATAN KABUPATEN WAKATOBI - Eviyanti Eviyanti (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study aims to find out and describe the function of the bhangka mbule-mbule ritual in the community in Mandati II Subdistrict, South Wangi-wangi District, Wakatobi Regency. This study uses Barbara Herrnstein Smith's theory; the commodification of culture for tourism. The method of this study is an ethnographic method with data collection techniques through observation and in-depth interviews. The data collected is descriptive qualitative. The results show that the mbule-mbule bhangka ritual was an expression of gratitude for the success of the harvest obtained by the community both from gardening and fishing activities. This bhangka mbule-mbule ritual has values and functions related to the life of the Mandati community, among others: sacred functions, religious functions, safety functions, health functions, artistic functions (entertainment), economic functions, and socio-cultural functions. Along with the progress of the times, the bangka mbule-mbule ritual experienced a shift in function from the sacred domain to the profane realm. The ideology of capitalism that goes into the realm of the values of the community tradition Mandati becomes a cultural value that can be used as a commodity which is certainly worth selling. Keywords: bhangka mbule-mbule, value, function, commodivication